2020
DOI: 10.1186/s12906-020-02937-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term treatment of Carvacrol on glucose metabolism in Streptozotocin-induced diabetic mice

Abstract: Background: Carvacrol is a food additive with various bioactivities, including reducing the blood glucose level as well as improvement of heart function, in diabetic mice. We explored the antihyperglycemic effect of carvacrol and its effect on the key hepatic enzymes accounting for glucose metabolism. Methods: A streptozotocin (STZ)-induced diabetes-mellitus model in mice was used. Mice were divided randomly into a control group, diabetic group, low dose carvacrol-treated diabetic group (10 mg/kg body weight [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…Inosine is a potent stimulator of insulin secretion from isolated mouse islet cells ( 32 ), but its relation with diabetes development in humans remains unknown. Carvacrol is a predominant constituent of essential oils and has well-known antioxidant, antimicrobial, antifungal, and anti-inflammatory properties ( 33 , 34 ), and exerted an anti-hyperglycemic effect in STZ-induced diabetic mice and a protective role in diabetes-induced aortic hypercontractility ( 35 , 36 ). In the present study, the OR associated with metabolites and clinical factors for the risk of diabetes after adjustment for confounding factors are analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Inosine is a potent stimulator of insulin secretion from isolated mouse islet cells ( 32 ), but its relation with diabetes development in humans remains unknown. Carvacrol is a predominant constituent of essential oils and has well-known antioxidant, antimicrobial, antifungal, and anti-inflammatory properties ( 33 , 34 ), and exerted an anti-hyperglycemic effect in STZ-induced diabetic mice and a protective role in diabetes-induced aortic hypercontractility ( 35 , 36 ). In the present study, the OR associated with metabolites and clinical factors for the risk of diabetes after adjustment for confounding factors are analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors associated the reduction in blood glucose to the hypoglycemic effects of carvacrol [ 55 , 56 , 57 , 58 ]. By improving insulin sensibility and promoting intracellular glucose uptake, carvacrol treatment may also prevent ROS production and oxidative damage [ 59 ]. To some extent, the energy stores depletion during stress exposure [ 26 ] could explain the poor growth rates observed with CD compared to D100.…”
Section: Discussionmentioning
confidence: 99%
“…Carvacrol in STZ-induced rats decreased random plasma glucose and fasting plasma glucose levels signifcantly in a dose-dependent manner. Carvacrol at a dose of 20 mg/kg in diabetic mice caused the decrease in plasma triglyceride level and signifcantly reduced plasma LDH level, but not AST, ALT, or ALP, and there was increased activity of hexokinase (HK), 6-phosphofructokinase (PFK), and citrate synthase (CS) [61]. Te study by Zhao et al [62] showed improvement in glucose and insulin resistance of T2DM db/db mice treated with 10 mg/kg carvacrol.…”
Section: Catalpolmentioning
confidence: 97%